2013
DOI: 10.1007/s00018-013-1310-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel siRNA delivery strategy: a new “strand” in CNS translational medicine?

Abstract: RNA interference has been envisaged as a powerful tool for molecular and clinical investigation with a great potential for clinical applications. In recent years, increased understanding of cancer biology and stem cell biology has dramatically accelerated the development of technology for cell and gene therapy in these areas. This paper is a review of the most recent report of innovative use of siRNA to benefit several central nervous system diseases. Furthermore, a description is made of innovative strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 191 publications
0
13
0
Order By: Relevance
“…The reduction or absence of the C-terminal domain has been previously observed in other dinoflagellates [ 68 ]. Evolutionarily, dinoflagellate KatGs belong to the minor KatG clades, which are intermediate between bifunctional KatGs and uni-functional peroxidases like APX (including hybrid APX-CcP) and cytochrome c peroxidases [ 69 ]. The observed SymKatG Inserts 1 and 3 are essentially an extension of the characteristic first and second KatG loop [ 70 ], while SymKatG Insert 2 is a unique feature only shared by Prorocentrum minutum .…”
Section: Discussionmentioning
confidence: 99%
“…The reduction or absence of the C-terminal domain has been previously observed in other dinoflagellates [ 68 ]. Evolutionarily, dinoflagellate KatGs belong to the minor KatG clades, which are intermediate between bifunctional KatGs and uni-functional peroxidases like APX (including hybrid APX-CcP) and cytochrome c peroxidases [ 69 ]. The observed SymKatG Inserts 1 and 3 are essentially an extension of the characteristic first and second KatG loop [ 70 ], while SymKatG Insert 2 is a unique feature only shared by Prorocentrum minutum .…”
Section: Discussionmentioning
confidence: 99%
“…However, this potential treatment for impaired learning also faces the major hurdle of attaining effective delivery to the CNS, which could provide a specific means to knock down the expression of targets involved in CNS diseases (24,25). Several reports showed that nanoparticle-linked siRNA can be delivered into the brain by intranasal administration to knock down target proteins (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the gene therapy toolbox was enriched by virally delivered shRNAs and microRNAs to knockdown disease‐associated proteins (Deng et al ., ; Gurevich et al ., ). Non‐viral methods of delivery of therapeutic siRNAs and microRNAs are actively being developed (Yuan et al ., ; Gherardini et al ., ). Despite multiple challenges (off‐target effects, immune response, delivery problems), siRNAs are considered very attractive for treatment of such deadly diseases as cancer (Petrocca and Lieberman, ) and HIV/AIDS (Zeller and Kumar, ), with several clinical trials already underway (Castanotto and Rossi, ; Burnett et al ., ; Petrocca and Lieberman, ).…”
Section: Gene Therapy and Genome Editingmentioning
confidence: 97%